Relationship between Physical Activities, Stress and Eating Patterns with the Risk of Hipertension in Women in Baiturrahman Community Health Centers Banda Aceh - Sari, Etika; Yusni, Yusni; Usman, Said; Syukri, Maimun; Yusuf, Hanifah (Budapest International Research and Critics University, 2020)
The pattern of disease events at this time has experienced a change marked by changes in disease and death that were originally dominated by infectious diseases switch to non-communicable diseases. In the 2018 Riskesdas results the prevalence of hypertension in Aceh increased compared to 2013. Purpose: to find out the factors associated with the incidence of hypertension in women at the Baiturrahman Health Center in Banda Aceh City. Research Methods: This research is a type of quantitative research with cross-sectional study design conducted on 124 samples. Sampling was carried out using the Accidental Sampling technique. Data analysis uses univariate, bivariate and multivariate. Statistical analysis using chi-square and logistic regression. Results: The results showed that there was a significant relationship between family history (p-value = 0.007, OR = 2.8), food consumption patterns (p-value = 0.025, OR = 2.5), obesity status (p-value = 0.046, OR = 2.2), Physical activity (p-value = 0.012, OR = 3.2) and Stress (p-value = 0.017, OR = 2.9) with the incidence of hypertension in women. Multivariate analysis results indicate that family history is a dominant factor in the incidence of hypertension (OR = 4.7). Conclusion: Family history, food consumption patterns, obesity, physical activity and stress are related to the incidence of hypertension and the most dominant factor in the incidence of hypertension in women in the working area of the Baiturrahman Health Center in Banda City is family history of hypertension.